(untitled) (Nordic Journal of Practical Theology, 2023)
The article reports results from a small-scale study of “special experiences” among clergy in the Norwegian Lutheran Church. The main purpose of the study was to find out how clergy relate to such experiences, based on the assumption that they, like the rest of the population, have experiences beyond the ordinary. This assumption was confirmed. Interestingly, many of them reported on such experiences linked to either their personal calling to become ministers, or these experiences closely related to their actual ministry. As a general conclusion, the study confirms that such experiences have impact on the faith and the conviction that God is behind them in their work as ministers.